2011
DOI: 10.1002/hlca.201000440
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Radical Cyclization of 3‐Oxopropanenitriles and Alkenes with Cerium(IV) Ammonium Nitrate in Ether Solvents

Abstract: The radical cyclization of 3-oxopropanenitriles 1a -1e and alkenes 2a -2g with cerium(IV) ammonium nitrate (CAN) in ether solvents was investigated (Tables 1 and 2). In the optimization study, 1,3-dioxolane, 1,4-dioxane, 1,2-dimethoxyethane, Et 2 O, and THF were used as ether-based solvents, and the latter was found to be the most effective solvent in radical cyclizations mediated by cerium(IV). This system (cerium(IV)/THF) was applied to cyclizations of various 3-oxopropanenitriles and 1,3-dicarbonyl compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…20 Regioselective synthesis of 2,3,4-trisubstituted pyrrole 10 has been achieved via [3,3] Three-component 1-pot condensation reactions of ethyl glycinate 11, 3-hydroxybutan-2-one 12, and 1 yielded ethyl 2-(3-cyano-4,5-dimethyl-2-phenyl-1H -pyrrol-1-yl)acetate 13, which was consequently hydrolyzed to produce the corresponding carboxylic acid 14 (Scheme 2). 9 4,5-Dihydro-3-furancarbonitrile derivatives 21 were obtained through radical cyclization of 1, mediated either by manganese(III) acetate in acetic acid 2,25,26 or by cerium(IV) ammonium nitrate in THF 27 with substituted ethylene 20. Cerium(IV)/THF radical cyclization was compared with that performed with manganese(III) acetate/AcOH; the cerium(IV)/THF system turned out to be much more efficient.…”
Section: Pyrroles and Their Fused Derivativesmentioning
confidence: 99%
“…20 Regioselective synthesis of 2,3,4-trisubstituted pyrrole 10 has been achieved via [3,3] Three-component 1-pot condensation reactions of ethyl glycinate 11, 3-hydroxybutan-2-one 12, and 1 yielded ethyl 2-(3-cyano-4,5-dimethyl-2-phenyl-1H -pyrrol-1-yl)acetate 13, which was consequently hydrolyzed to produce the corresponding carboxylic acid 14 (Scheme 2). 9 4,5-Dihydro-3-furancarbonitrile derivatives 21 were obtained through radical cyclization of 1, mediated either by manganese(III) acetate in acetic acid 2,25,26 or by cerium(IV) ammonium nitrate in THF 27 with substituted ethylene 20. Cerium(IV)/THF radical cyclization was compared with that performed with manganese(III) acetate/AcOH; the cerium(IV)/THF system turned out to be much more efficient.…”
Section: Pyrroles and Their Fused Derivativesmentioning
confidence: 99%
“…However, recently we performed an optimization study on the radical addition of 3-oxopropanenitriles to alkenes using CAN in ethereal solvents, resulting CAN / THF system formed dihydrofurans in high yields on mild condition. 42 In the present study, we applied the previous method to reactions of 1,3-dicarbonyl compounds with conjugated dienes promoted CAN / THF and obtained 2-(2-phenylethenyl) substituted 4,5-dihydrofurans as regioselectively in excellent yields.…”
Section: Introductionmentioning
confidence: 97%
“…Manganese (III) acetate [29][30][31][32][33] and cerium(IV) ammonium nitrate (CAN) [34][35][36][37][38] are widely used in these reactions. Our research group has reported radical addition and cyclization reactions with CAN [39][40][41][42] and radical cyclization reactions of 1,3-dicarbonyl derivatives with various unsaturated systems, such as conjugated amide derivatives [43][44][45][46][47]and heteroaromatic conjugated alkenes [48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%